2004
DOI: 10.2514/1.4265
|View full text |Cite
|
Sign up to set email alerts
|

Flow Around a Rotatable Circular Cylinder-Plate Body at Subcritical Reynolds Numbers

Abstract: The behavior of a stationary circular cylinder with an attached plate, under conditions where the entire cylinderplate body rotates about the cylinder axis, has been investigated experimentally for Reynolds numbers between 8 × × 10 3 and 6 × × 10 4 . To see the effect of the plate inclination on the pressure distributions and vortex shedding, the cylinder-plate body was rotated from 0 to 180 deg, unlike freely rotatable cases in previous studies. The plate was located at the center plane of the cylinder, upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Drag coefficients were found at maximum and minimum values at 75 and 15 degree, respectively. While lift coefficient was observed to have two maximum values at the 15 and 165 degrees and minimum values were 0, 45, 158 and 180 degree [4].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Drag coefficients were found at maximum and minimum values at 75 and 15 degree, respectively. While lift coefficient was observed to have two maximum values at the 15 and 165 degrees and minimum values were 0, 45, 158 and 180 degree [4].…”
Section: Introductionmentioning
confidence: 90%
“…Apelt et al reported that they examined splitter plate behind circular cylinder in range of L/D2 at Reynolds numbers between 10 4 and 5x10 4 . They depicted that using a splitter plate reduces drag and produces narrower wake than that of bare cylinder.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations